Values of Coagulation Function Indices in Distinguishing between Acute Ischemic Stroke Patients with and without Non-Valvular Atrial Fibrillation - Du, Qing; Zhao, Xiaohui; Song, Haixia; Jiang, Ju; Zheng, Kaiming; Zhang, Yuezhan (Journal of Medical Biochemistry, 2025)
Background: Treatment strategies differ in acute ischemic stroke (AIS) patients with and without non-valvular atrial fibrillation (NVAF). It remains unclear whether coagulation function indices can be used to distinguish between the two conditions. Methods: In this retrospective study, AIS patients with NVAF (AIS with NVAF group, n=43) and without NVAF (AIS without NVAF group, n=90) admitted to Lianyungang Affiliated Hospital of Nanjing University of Chinese Medicine, were enrolled for final analysis. The levels of coagulation function indices, including DD, APTT, PT, INR, TT, and fibrinogen were tested before or on admission and compared between the two groups. Results: Compared with AIS without NVAF group, DD, PT, and INR were increased and APTT was decreased in AIS with NVAF group (P<0.05), whereas, there were no significantly statistical differences of TT and fibrinogen (P<0.05); next, the AUC in distinguishing between AIS with and without NVAF were 0.753, 0.761, 0.775, and 0.770 for DD, APTT, PT, and INR, respectively (P<0.05). Conclusions: DD, APTT, PT and INR showed certain reference value for the differential diagnosis of AIS patients with or without NVAF.